Glacial Geology and Geomorphology of the Sortehjorne Area, East Greenland - Pessl, Jr., Fred (ARCTIC, 1962)
Reports studies in 1959 and 1961 of glacial features in five valleys of this area (approx. 72 N, 24 W) near Mesters Vig. Moraines, erratics, striae, kame terraces, emerged marine deltas, and glacial control of drainage patterns are described. Evidence from these features indicates that: during maximum glaciation, the ice margin extended considerably beyond the present coastline; the higher peaks were nunataks; deglaciation was primarily by lateral thinning and downwasting; the sea was at least 75 meters above its present level; a minor readvance of the glaciers occurred in recent time; and the isostatic adjustment of the land caused rejuvenation of the streams, with extensive canyon cutting.